Sustaining and Strengthening Indonesia Art and Culture - AM Hermien Kusmayati (Institut Seni Indonesia Yogyakarta, 2018)
AbstractThis study aims to analyze the background and sustainability of plurality or diversity of Indonesian art and culture in the form of implementation as a revitalization of traditional performing arts. Qualitative research with an ethnographic approach and an emic and ethical point of view are employed to observe it. The richness of art —both material and non-material with its various aspects are created through struggles against nature, space, and time which are not always easy to address. The cone-shaped cultural wealth as an art is created from the depths of consciousness, understanding, and insight which are not simple but bearing various symbols. The use of symbols in the form of art lengthens its roots from one generation to the next as a representation of the clarity and wisdom of the crystallization of the intelligence of feelings and thoughts. Informal and non-formal educations are efforts which can be done by the present generation to confirm its sustainability. In the vastness of a very open global era, as intercultural interactions intensify, a strong and resilient culture is needed. As something inherited, the future sustainability lies in the hands of the generation, i.e. the society of the recipients in the present and the future.Keywords: Indonesian art; traditional dance; batik; mamacaAbstrakKeberlanjutan dan Penguatan Seni-Budaya. Penelitian ini bertujuan untuk menganalisis latar belakang dan keberlanjutan pluralitas atau keberagaman seni budaya Indonesia dalam wujud pelaksanaan sebagai suatu revitalisasi seni pertunjukan tradisi. Penelitian kualitatif dengan pendekatan etnografis dan sudut pandang emik serta etik ditempatkan untuk mencermatinya. Kekayaan seni – budaya baik bendawi maupun non bendawi dengan berbagai aspeknya diciptakan melalui pergulatan terhadap alam, ruang, dan waktu yang tidak selalu mudah disikapi. Kekayaan budaya yang mengerucut sebagai seni yang diciptakan dari kedalaman kesadaran, pemahaman, serta penghayatan yang tidak sederhana bermuatan berbagai simbol. Penggunaan simbol-simbol dalam wujud seni, memanjangkan akarnya dari satu generasi ke generasi berikutnya sebagai representasi kejernihan dan kearifan dari kristalisasi kecerdasan perasaan dan pikiran. Melalui dan di dalam pendidikan baik formal maupun non formal adalah upaya yang dapat dilakukan oleh generasi sekarang untuk meneguhkan keberlanjutannya. Di keluasan era global yang sangat terbuka, ketika interaksi kebudayaan antarbangsa semakin intensif, sungguh diperlukan ketahanan budaya yang sangat kuat dan tangguh. Sebagai sesuatu yang diwariskan, maka kelanjutannya di masa depan berada di tangan generasi pewarisnya, yaitu masyarakat penerimanya pada saat sekarang maupun yang akan datang.Kata kunci: kesenian Indonesia; tari tradisi; batik; mamaca